SIMON VANDE WALLE Private Antitrust Litigation in the European Union and Japan - Heath, Christopher (Zeitschrift für Japanisches Recht, 2013)
SIMON VANDE WALLE Private Antitrust Litigation in the European Union and Japan Maklu Publications, Antwerpen and Apeldoorn 2013, Diss. Kyūshū Universität; 355 S., € 95.00; ISBN 9789046605264 <img style="border: 0px none; height: 16px; width: 16px; display: inline;" title="Titel anhand dieser ISBN in Citavi-Projekt übernehmen" src="data:image/png;base64,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" alt="" /> <img style="border: 0px none; height: 16px; width: 16px; display: inline;" title="Titel anhand dieser ISBN in Citavi-Projekt übernehmen" src="data:image/png;base64,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" alt="" />